Analisa debit banjir rancangan Bendungan Palasari menggunakan HEC-HMS - Ni Luh Putri Prabandari; I Putu Gustave Suryantara Pariartha; Silvia Gabrina Tonyes (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
The Palasari Dam is a rock fill structure with a flood storage capacity of 10.37 million m³ and encompasses a catchment area of 40.75 km². In recent years, catastrophic climate changes have caused considerable variations between drought and intense rainfall, heightening the danger of dam failure owing to abrupt increases in water volume. This study is to assess the anticipated flood flow in the Palasari Watershed utilizing the Soil Conservation Service-Curve Number (SCS-CN) methodology within the HEC-HMS software. The utilized data include maximum annual rainfall from the CHIRPS satellite for the years 2004 to 2023, land use information retrieved from the Indonesia Geospatial Portal, and soil type data derived from HWSD v.2 (FAO). Simulations were performed for recurrence intervals of 5, 10, 25, 50, 100, and 1000 years, in addition to the Probable Maximum Flood (PMF). Validation indicates that the SCS approach in HEC-HMS yields greater flood discharge predictions than the Nakayasu method utilized in the 2018 Special Study of the Palasari Dam. The minimum discharge recorded at a 5-year return period was 64.60 m³/second, whilst the maximum discharge reached during the Probable Maximum Flood (PMF) was 710.70 m³/second. A notable discrepancy is evident in QPMF, with the SCS method documenting a discharge of 710.70 m³/second, surpassing the Nakayasu method's output of 686.07 m³/second. The SCS-CN method demonstrates a more conservative approach in calculating flood discharge, hence enhancing the safety margin in dam planning. Conversely, HEC-HMS offers advantages in assessing lag time and its integration with GIS, rendering it a more pragmatic method for water resource management in Indonesia. This research significantly enhances the formulation of Emergency Action Plans (EAP), especially in the context of dam failure analysis, aimed at mitigating risks associated with high flooding.